Unrecorded Berwickshire antiquities - Kinghorn, Robert (Proceedings of the Society of Antiquaries of Scotland, 1935)
1. Siccar Point Fort 2. Corn Fort, Hareness Point 3. Lamberton Shiels Fort 4. Hareheugh Craigs Fort 5. Haly Jo Fort 6. Pettico Wick Fort 7. Brander Heugh Fort 8. Greenlaw Rock 9. Camp Field Fort 10. Homestead, Pilmuir, Lauder 11. Black Dyke, with Pitted Trench, Lamberton Moor 12. Cultivation Terraces, Chester Hill, Ayton Parish 13. Small Cairns, Wheelburn Law